Interventional Cardiology - Akin, Ibrahim (IntechOpen, 2017)
The development of innovative interventional strategies and materials, primarily attributed to rapid strides in healthcare technology and education, has helped position interventional cardiology as one of the foremost disciplines in cardiovascular medicine. Patients diagnosed with inoperable conditions, including complex structural heart disease, have found renewed hope with the practice of these path-breaking therapeutic techniques. Nevertheless, the growing complexity of these procedures has also necessitated a close cooperation with different specialists, such as cardiothoracic surgeons, vascular surgeons, anesthesiologists, and interventional radiologists. There is an urgent need to further explore the use of such alternative strategies of clinical management of cardiac disease, while limiting or potentially eliminating any procedural risks for the patient. This book is oriented to readers interested in learning the basic principles of interventional cardiology and offers a brief insight into the potential use of such treatments in routine clinical practice.